2020
DOI: 10.1159/000507221
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Lower Lid Margin Thickness by Anterior Segment Optical Coherence Tomography

Abstract: Purpose: To verify the feasibility of using anterior segment optical coherence tomography (AS-OCT) to measure the lower lid margin thickness (LLMT) from posterior lash line to the mucocutaneous junction. Methods: This was a prospective, single-center, observational study. Fifty-six volunteers between 20 and 79 years old with normal healthy eyes were included in this study. Using AS-OCT to measure the LLMT at the middle position was separately performed by two operators under the same conditions. Results: The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…Previous studies [8,28] had shown that the lid margin thickened with age because of enlargement of the orbicularis and meibomian glands in the first 20 years of life, but the LMT in adults did not change with age. Contrary to the above conclusions, our present and previous studies [15,17] suggested that the LMT, especially the lower LMT, also seemed to be related to age. This further supported the literature reports on age-related changes in the lid margin anatomy [3,8,28] and the theory that the incidence of MGD increased with age [2][3][4][5][6][7].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous studies [8,28] had shown that the lid margin thickened with age because of enlargement of the orbicularis and meibomian glands in the first 20 years of life, but the LMT in adults did not change with age. Contrary to the above conclusions, our present and previous studies [15,17] suggested that the LMT, especially the lower LMT, also seemed to be related to age. This further supported the literature reports on age-related changes in the lid margin anatomy [3,8,28] and the theory that the incidence of MGD increased with age [2][3][4][5][6][7].…”
Section: Discussioncontrasting
confidence: 99%
“…Although the LMT is difficult to measure, people are still trying to measure it with several different methods [15][16][17][28][29][30]. Hykin et al [8] suggested that the lid margin width in normal adults including wet mucosa was approximately 2.5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations